Influence of the W and Ta content on the High-Temperature Oxidation Resistance of Multinary Co/Ni-Based Superalloys at 1050 °C and 1150 °C - Hagen, Sebastian; Haußmann, Lukas; Wahlmann, Benjamin; Gebhardt, Franz; Abu-Khousa, B.; Weiser, Martin; Neumeier, Steffen; Zenk, Christopher; Virtanen, Sannakaisa (High Temperature Corrosion of Materials, 2023)
Outstanding inherent environmental resistance is a precondition for the use of superalloys in high-temperature applications. Besides high Al and Cr levels, also refractory metal concentrations (W and Ta) are reported to affect protective scale formation, as these elements are expected to affect the chemical activity and also the transport of protective scale formers within the alloy. In this study, we elucidate the high-temperature oxidation behavior of 3 Co-based (Co/Ni ratio: 1.4) and 3 Ni-based (Co/Ni ratio: 0.7) superalloys differing in W and Ta levels. Time-resolved thermogravimetric analysis (TGA) in synthetic air at 1050 °C and 1150 °C for 100 h, scanning electron microscopy analysis (SEM), thermodynamic calculations using the CALPHAD software Thermo-Calc, and diffusion couple experiments were conducted to assess the impact of the Co/Ni ratio and the refractory metal content on the oxidation performance. The results indicate that a low W content (3 vs. 5 at.%) and a high Ta content (2.1 vs. 1.5 at.%) beneficially affect the oxidation resistance, as alumina scale formation is facilitated.
Created from Fastlane, Scopus look-up
Keywords: Cobalt-base superalloys; High-temperature oxidation; Protective scales; Refractory metals